2017
DOI: 10.1242/dev.144097
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA-mRNA expression network during oral siphon regeneration in Ciona

Abstract: Here we present a parallel study of mRNA and microRNA expression during oral siphon (OS) regeneration in Ciona robusta, and the derived network of their interactions. In the process of identifying 248 mRNAs and 15 microRNAs as differentially expressed, we also identified 57 novel microRNAs, several of which are among the most highly differentially expressed. Analysis of functional categories identified enriched transcripts related to stress responses and apoptosis at the wound healing stage, signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 112 publications
1
19
0
Order By: Relevance
“…The ability to precisely edit the genomes of a variety of organisms has greatly expanded the usefulness of these systems as models for human development and disease (Cardi, D'Agostino, & Tripodi, ; Chen et al, ; Singh, Braddick, & Dhar, ). Ascidians are gaining prominence as excellent models for examining a wide variety of biological problems including regeneration (Spina, Guzman, Zhou, Kosik, & Smith, ), Alzheimer's studies (Virata & Zeller, ), and climate change research (Lopez et al, ). The ascidian embryo also provides a rapid and useful system for the analysis of complex regulatory elements (Farley et al, ; Kusakabe, ; Satou & Imai, ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to precisely edit the genomes of a variety of organisms has greatly expanded the usefulness of these systems as models for human development and disease (Cardi, D'Agostino, & Tripodi, ; Chen et al, ; Singh, Braddick, & Dhar, ). Ascidians are gaining prominence as excellent models for examining a wide variety of biological problems including regeneration (Spina, Guzman, Zhou, Kosik, & Smith, ), Alzheimer's studies (Virata & Zeller, ), and climate change research (Lopez et al, ). The ascidian embryo also provides a rapid and useful system for the analysis of complex regulatory elements (Farley et al, ; Kusakabe, ; Satou & Imai, ).…”
Section: Discussionmentioning
confidence: 99%
“…We used published RNA sequencing (RNA-Seq) data sets for N. vectensis (Schaffer et al. 2016), H. vulgaris , C. intestinalis (Spina et al. 2017), and S. mediterranea (Zeng et al.…”
Section: Methodsmentioning
confidence: 99%
“…2015). Read counts for C. intestinalis were estimated according to our previously published procedure (Spina et al. 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In Ciona robusta, previously known as C. intestinalis type A [28], miR-9 was found to be expressed at gastrula and larval stages [26]. In this species, through a transcriptome-wide study of gene expression of both mRNA and microRNA, it was found that miR-9 is upregulated during oral siphon regeneration and is involved in the differentiation of neural progenitors through regulation of the cytoskeleton and cell cycle [29]. This pro-neural function of miR-9 is conserved between ascidians and vertebrates, in which one of its key functions is to regulate the generation of postmitotic neurons from neural precursor cells [30].…”
Section: Introductionmentioning
confidence: 99%